2001
DOI: 10.1088/0264-9381/18/6/501
|View full text |Cite
|
Sign up to set email alerts
|

BF gravity and the Immirzi parameter

Abstract: The publishers would like to apologize for an error occurring in issue 5 (7 March 2001) of Classical and Quantum Gravity. The article by Capovilla et al was published as a Letter to the Editor, when it should have appeared as a Paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 0 publications
1
51
0
Order By: Relevance
“…The first BF principle to describe pure gravity including the Immirzi parameter was introduced in Ref. [12] and is given by…”
Section: Hamiltonian Analysis Of the Cmpr Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first BF principle to describe pure gravity including the Immirzi parameter was introduced in Ref. [12] and is given by…”
Section: Hamiltonian Analysis Of the Cmpr Actionmentioning
confidence: 99%
“…Afterwards, Holst introduced a modification of the Hilbert-Palatini action and it was showed that Barbero's formulation was the Hamiltonian form of this action principle [8,9]. Moreover, real general relativity was also written as a constrained BF theory [10,11] and later works generalized the constraint on the B field [12,13] in such a way that by solving it the Immirzi parameter γ [14], a free parameter appearing in Barbero's formulation, was naturally included.…”
Section: Introductionmentioning
confidence: 99%
“…One way to overcome the problem is to modify the Plebanski theory such that it does not admit the topological solutions anymore. There is a way to do so [20] but the price to pay is that classical solutions are those of gravity with an Immirzi parameter γ supplemented with those of gravity with the inverse parameter γ −1 . Thus, the path integral can be performed and can be shown, as expected, to mix both types of solutions.…”
mentioning
confidence: 99%
“…al. (CMPR action) [9] but before we integrate out the metric variable in this action, we will give some details over the Cartan-Killing form and the auxiliary fields, so that we'll obtain an adequate pure connection formulation from where maximally symmetric spaces will appear as solutions from its variational principles. The organization of the paper is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…At the middle of the seventies of the last century, Plebański considered self-dual quantities by a complexified SO(3) group, but in order to describe Lorentzian signature spacetime it was necessary to impose certain reality conditions [11]. Here, we consider one of the most well-known BF action functional which give rise to an action for GR with Immirzi parameter [9], by considering SO(1, 3) as our internal symmetry group…”
Section: Introductionmentioning
confidence: 99%